Impact of Age and HIV Status on Immune Activation, Senescence and Apoptosis - Hove-Skovsgaard, Malene; Zhao, Yanan; Tingstedt, Jeanette Linnea; Hartling, Hans Jakob; Thudium, Rebekka Faber; Benfield, Thomas; Afzal, Shoaib; Nordestgaard, Børge; Ullum, Henrik; Gerstoft, Jan; Mocroft, Amanda; Nielsen, Susanne Dam (Frontiers in Immunology, 2020)
Residual immune dysfunctions, resembling those that occur during normal aging, may persist even in well-treated people with HIV (PWH), and accelerated aging has been proposed. We aimed to determine if HIV infection is an independent risk factor for T-cell immune dysfunctions including increased immune activation, senescence and apoptosis. Moreover, in PWH we aimed to identify the associations between age and immune activation, senescence and apoptosis. We included 780 PWH with suppressed viral replication (<50 copies/mL) and absence of hepatitis B and hepatitis C co-infection and 65 uninfected controls from the Copenhagen Co-morbidity in HIV Infection (COCOMO) Study. Flow cytometry was used to determine T-cell activation (CD38+HLA-DR+), senescence (CD28-CD57+) and apoptosis (CD28-CD95+). T-cell subsets are reported as proportions of CD4+ and CD8+ T-cells. We defined an elevated proportion of a given T-cell subset as above the 75th percentile. Regression models were used to determine the association between HIV status and T-cell subset and in PWH to determine the association between age or HIV-specific risk factors and T-cell subsets. Furthermore, an interaction between HIV status and age on T-cell subsets was investigated with an interaction term in models including both PWH and controls. Models were adjusted for age, sex, BMI and smoking status. In adjusted models a positive HIV status was associated with elevated proportions of CD8+ activated (p=0.009), CD4+ senescent (p=0.004), CD4+ apoptotic (p= 0.002) and CD8+ apoptotic (p=0.003) T-cells. In PWH a 10-year increase in age was associated with higher proportions of CD4+ and CD8+ senescent (p=0.001 and p<0.001) and CD4+ and CD8+ apoptotic T-cells (p<0.001 and p<0.001). However, no interaction between HIV status and age was found. Furthermore, in PWH a CD4+/CD8+ ratio <1 was associated with elevated proportions of T-cell activation, senescence and apoptosis. We found evidence of residual T-cell immune dysfunction in well-treated PWH without HBV or HCV co-infection, and age was associated with T-cell senescence and apoptosis. Our data supports that HIV infection has similar effects as aging on T-cell subsets. However, since no interaction between HIV status and age was found on these parameters, we found no evidence to support accelerated immunological aging in PWH.